2006
DOI: 10.1101/gad.1482006
|View full text |Cite
|
Sign up to set email alerts
|

The RNA silencing endonuclease Argonaute 2 mediates specific antiviral immunity in Drosophila melanogaster

Abstract: Most organisms have evolved defense mechanisms to protect themselves from viruses and other pathogens.Arthropods lack the protein-based adaptive immune response found in vertebrates. Here we show that the central catalytic component of the RNA-induced silencing complex (RISC), the nuclease Argonaute 2 (Ago-2), is essential for antiviral defense in adult Drosophila melanogaster. Ago-2-defective flies are hypersensitive to infection with a major fruit fly pathogen, Drosophila C virus (DCV), and with Cricket Para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
572
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(596 citation statements)
references
References 41 publications
19
572
2
3
Order By: Relevance
“…In yeast, the heterochromatic repeats need to be transcribed to generate siRNA that positively regulates heterochromatin formation (Volpe et al, 2002). A similar system has been described in Drosophila (Pal-Bhadra et al, 2004;van Rij et al, 2006;Wang et al, 2006). The described mechanisms involve deactylation of H3K9Ac by HDAC1, demethylation of H3K4 by LSD1 and KDM2A, methylation of H3K9 or H3K23 and binding of HP1 (Schotta et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, the heterochromatic repeats need to be transcribed to generate siRNA that positively regulates heterochromatin formation (Volpe et al, 2002). A similar system has been described in Drosophila (Pal-Bhadra et al, 2004;van Rij et al, 2006;Wang et al, 2006). The described mechanisms involve deactylation of H3K9Ac by HDAC1, demethylation of H3K4 by LSD1 and KDM2A, methylation of H3K9 or H3K23 and binding of HP1 (Schotta et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Ago2-defective flies are hypersensitive to infection with a major fruit fly pathogen, Drosophila C virus (DCV), Flock House virus (FHV), and with Cricket Paralysis virus (CrPV). Increased mortality in ago2 mutant flies was associated with a dramatic increase in viral RNA accumulation and virus titers [21,22]. In fishes, Argonaute family homologous sequences were only found from three species in GenBank searched by Blastp.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that many human viruses can productively infect Drosophila S2 cells including Vesicular Stomatitis Virus, Sindbis Virus, Rift Valley Fever Virus, Dengue virus, West Nile Virus ( [51,52] and our unpublished data). The insect-specific viruses, Flock House Virus and Drosophila C virus (DCV) have also been extensively studied in fruit flies [51][52][53][54][55][56]. The first genome-wide RNAi screen for host factors that impact pathogen replication was performed using DCV infection of S2 cells [53].…”
Section: Viral Screensmentioning
confidence: 99%